2017
DOI: 10.1038/ijo.2017.169
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat and total energy intake modifies the association of genetic profile risk score on obesity: evidence from 48 170 UK Biobank participants

Abstract: Celis- Morales, C. et al. (2017) Dietary fat and total energy intake modifies the association of genetic profile risk score on obesity: evidence from 48 170 UK Biobank participants. International Journal of Obesity, 41, pp. 1761Obesity, 41, pp. -1768Obesity, 41, pp. . (doi:10.1038Obesity, 41, pp. /ijo.2017 This is the author's final accepted version.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.htt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 33 publications
(51 reference statements)
2
19
0
1
Order By: Relevance
“…Additionally, a study in 1680 South Asians has shown a significant interaction of the risk allele 'T' of the TCF7L2 SNP rs12255372 with fat intake on high-density lipoprotein cholesterol (HDL-C) [70]. Studies on GRS-diet interactions on obesity traits have mainly focused on European populations [71][72][73]. In agreement with our study, data from UK Biobank [72] and two studies from the US [71] have reported significant interactions between the GRS and dietary intakes of total fat and SFA on WC; the GRS was associated with a higher WC among individuals with high intakes of total fat and SFA.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study in 1680 South Asians has shown a significant interaction of the risk allele 'T' of the TCF7L2 SNP rs12255372 with fat intake on high-density lipoprotein cholesterol (HDL-C) [70]. Studies on GRS-diet interactions on obesity traits have mainly focused on European populations [71][72][73]. In agreement with our study, data from UK Biobank [72] and two studies from the US [71] have reported significant interactions between the GRS and dietary intakes of total fat and SFA on WC; the GRS was associated with a higher WC among individuals with high intakes of total fat and SFA.…”
Section: Discussionmentioning
confidence: 99%
“…According to a 2-year weight loss intervention programme, carriers of the risk allele 'A' of the FTO SNP rs1558902 had a greater reduction in weight and regional fat compared to non-carriers when high protein diets were consumed, whereas an opposite genetic effect was found on changes in fat distribution in response to a low-protein intake [60]. However, studies investigating the joint effect of genetic variants have reported conflicting results [62][63][64], indicating that the influence of genetic predisposition on changes in body weight and WC does not seem to be modulated by protein intake. In contrast, the present study provides evidence for GRSprotein intake interactions on WC and triglyceride concentrations, and these interactions were independent of potential confounding effects.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with some studies [62,63], no interactions were detected between GRS and dietary intake of protein, fat and carbohydrate on BMI in the present study. However, a study in the European population (N = 48,170 adults) has shown that the joint effect of 93 obesity-related SNPs on BMI might be modulated by the intake of total energy, fat and saturated fat [64]. Furthermore, studies have shown that an obesogenic diet and physical inactivity with relatively high intake of sugar-sweetened beverages and prolonged television watching might exaggerate the effect of genetic factors on adiposity [18,68].…”
Section: Discussionmentioning
confidence: 99%
“…Diet (particularly fat and energy intake) has been shown to interact with genetic risk scores to alter the obesity risk. 79 Genes implemented in diet-gene interactions in obesity namely include FTO, MC4R, APOA2, PLIN and PPARG genes. FTO is regarded as the first identified obesity gene.…”
Section: Obesitymentioning
confidence: 99%